Exploitation of Social Networking Sites and Its Impacts on Students Academic Results: A Quest for Correlation or Misspecification in Bangladesh (Journal of Business and Technology (Dhaka), 2015)
Social networking sites have become the inevitable part of everyones life. Large numbers of students in Bangladesh spend a lion share of daily time by wandering through online social networking sites. So it is imperative to mention the effects of using social networking sites on the society. This study aims to analyse whether the use of social networking sites can influence students academic results or not. To get the desired answer, a random sample, constituted with 1182 university students from Dhaka Metropolitan City, Bangladesh, was drawn and surveyed with self-administered questionnaire. This study significantly found that, students achieved average results in last two semesters were inversely influenced by their hours of regular involvement in different social networking sites (SNSs), and also by the use of different mobile messaging applications (MMAs). Based on the finding, this study concludes that, students involvement in different SNSs and MMAs in terms of hours should be closely monitored to mitigate the aforesaid inverse effects. DOI: http://dx.doi.org/10.3329/jbt.v9i1.22777 Journal of Business and Technology (Dhaka) Vol.9(1) 2014; 23-51